A History of the Span of Management - Fleet, David D. Van; Bedeian, Arthur G. (Academy of Management Review, 1977)
This historical essay provides new insight into the span of management concept through an integration of the diverse literature on the topic. Early and ancient approaches are expanded upon; an encyclopedic bibliography is provided; and current conceptual models are identified.